Phage Predation Shapes the Population Structure of Shiga-Toxigenic Escherichia coli O157:H7 in the UK: An Evolutionary Perspective - Cowley, Lauren A.; Dallman, Timothy J.; Jenkins, Claire; Sheppard, Samuel K. (Frontiers in Genetics, 2019)
Natural genetic diversity in bacteria reflects interactions with the host environment, the resident microbiome and selection through predatory lytic bacteriophages. In studies of human and animal gut bacteria, it is important to consider the role of these phages in the host-pathogen milieu. We use an important zoonotic pathogen Shiga toxigenic Escherichia coli (STEC) O157:H7 to investigate this. Our study provides evidence that phage resistance profiles are well maintained at the sub lineage level with variation in profiles within sub lineages being uncommon. This indicates that phage resistance heterogeneity happened early on in the STEC O157:H7 natural history and that occasional “wobbles” don’t often outcompete the stable lineage unless combined with a competitive advantage. We discuss an example of this in the acquisition of stx2a that, while an important virulence factor, also conveys increased phage cross-resistance. We also discuss the role of phage resistance in co-occurrence of the three stable lineages worldwide and whether differing phage resistance is maintaining diversity and shaping the host-associated bacterial population.